2019
DOI: 10.1016/j.psyneuen.2018.12.223
|View full text |Cite
|
Sign up to set email alerts
|

Novel method of measuring chronic stress for preterm infants: Skin cortisol

Abstract: Background and objectives-Infants who begin life in the medicalized environment of the neonatal intensive care unit (NICU) do so under stressful conditions. Environmental exposures are often abrasive to vulnerable infants, while invasive and noninvasive lifesaving interventions provide additional pain and/or stress. The most commonly selected biomarker to measure stress is cortisol. The skin is the barrier between the external environment and communicates with our neurological, endocrine and immune regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Support for this hypothesis can be found in the work of A.L. D'Agata et al (35) who found that the number of stressful events in the previous 7 days correlated with skin cortisol in hospitalized preterm infants. In that study, skin cortisol was not associated with stressful events over a shorter timeframe, i.e.…”
Section: Discussionmentioning
confidence: 83%
“…Support for this hypothesis can be found in the work of A.L. D'Agata et al (35) who found that the number of stressful events in the previous 7 days correlated with skin cortisol in hospitalized preterm infants. In that study, skin cortisol was not associated with stressful events over a shorter timeframe, i.e.…”
Section: Discussionmentioning
confidence: 83%
“…Having no differences in mean cortisol levels over time might make it more difficult to identify differences in infant’s outcomes. The other explanation is that cortisol levels were higher among neonates with smaller gestational age that altered HPA axis (D’Agata et al, 2019) and those levels were highest during the first week, then gradually decreased by the first month (Greaves et al, 2014). Altered HPA axis due to elevated cortisol levels might change with time as a negative association between cortisol levels and motor development was reported at 6 months in VLBW female infants (Cho et al, 2017) while no association was reported under 24 months in full-term infants (Macari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…VLBW infants who were exposed to multiple noxious stimuli in the NICU showed high cortisol levels, especially infants with gestational ages smaller than 28 weeks (D’Agata et al, 2019). Repeated noxious stimuli might increase allostatic load and cause problematic health and development.…”
mentioning
confidence: 99%
“…Depending on the severity of illness or level of immaturity, many of the interventions performed are repeated over the course of the NICU stay 2. Although these procedures and interventions may be necessary for lifesaving measures, many of the everyday common nursing procedures are performed on a frequent, repetitive basis that can result in stressful and painful2 experiences that have cumulative and adverse effects on developmental outcomes. Studies have demonstrated that the frequency of medical and nursing procedures performed per infant includes the experience of 10 painful procedures per day and 38 handling interactions during a 24-hour period 3…”
Section: Background and Significancementioning
confidence: 99%